Dijet Azimuthal Decorrelations in pp Collisions at root s=7 TeV - Khachatryan, V. (2011)
Measurements of dijet azimuthal decorrelations in pp collisions at root s = 7 TeV using the CMS detector at the CERN LHC are presented. The analysis is based on an inclusive dijet event sample corresponding to an integrated luminosity of 2: 9 pb(-1). The results are compared to predictions from perturbative QCD calculations and various Monte Carlo event generators. The dijet azimuthal distributions are found to be sensitive to initial-state gluon radiation.